Mapping global justice: perspectives, cases and practice - Kurze, Arnaud (Global issues in crime and justice, 2023)
Persistent international conflicts, increasing inequality in many regions or the world, and acute environmental and climate-related threats to humanity call for a better understanding of the processes, actors and tools available to face the challenges of achieving global justice. This book offers a broad and multidisciplinary survey of global justice, bridging the gap between theory and practice by connecting conceptual frameworks with a panoply of case studies and an in-depth discussion of practical challenges. Connecting these critical aspects to larger moral and ethical debates is essential for thinking about large, abstract ideas and applying them directly to specific contexts. Core content includes: Key debates in global justice from across philosophy, postcolonial studies, political science, sociology and criminology The origins of global justice and the development of the human rights agenda; peacekeeping and post-conflict studies Global poverty and sustainable development Global security and transnational crime Environmental justice, public health and well-being Rather than providing a blueprint for the practice of global justice, this text problematizes efforts to cope with many justice related issues. The pedagogical approach is designed to map the difficulties that exist between theory and praxis, encourage critical thinking and fuel debates to help seek alternative solutions. Bringing together perspectives from a wealth of disciplines, this book is essential reading for courses on global justice across criminology, sociology, political science, anthropology, philosophy and law.